Embodied Othering Encounters with Muslim(‐Looking) Passengers: Riding across Amsterdam, Tallinn, Leipzig, and Turku. Issue 2 (2nd March 2022) - Shaker, Reza; Jungmann, Annika; Zimmermann, Philipp; Häkkinen, Lotta; Tuvikene, Tauri
Abstract : Often framed in the public discourse as Europe's ultimate Other, Muslims have been heftily debated and vastly problematized as violent, unfaithful suspect citizens, unwanted immigrants, part of a bad diversity, and refusal of modernity. Taking the Muslim Other into consideration, we explore young Muslim(‐looking) passengers' everyday Othering encounters within the (im)mobile spaces of public transport that entangle their bodies with different imaginaries, histories, emotions, and affects. Employing qualitative research methods in a cross‐national and interurban study in Amsterdam, Tallinn, Leipzig, and Turku, which offer different dimensions of diversity, size, and history, important for understanding European cities in their complexities, we present public transport as a cross‐cultural meeting place with socio‐spatial negotiations of difference to study everyday travel experiences of 74 young Muslim(‐looking) passengers. We highlight how Othering discourses become part of their everyday travel experiences. In so doing, we investigate multiple modes through which the Muslim Other is (re)produced and Othering is lived out in the networks of their everyday embodied, that is, sensorial, corporeal, and affective, experiences of public transport. In this way, we critically position public transport at the intersection of what it means to experience European cities through riding public transport.